2021
DOI: 10.1136/bmjopen-2020-048336
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian gland dysfunction and primary Sjögren’s syndrome dry eye: a protocol for systematic review and meta-analysis

Abstract: IntroductionPrimary Sjögren’s syndrome (pSS) is a systemic autoimmune disorder that primarily affects the exocrine glands such as the lacrimal and the salivary glands. Dry eye disease (DED) is one of the most prevalent manifestations of pSS and is usually classified into aqueous-deficient dry eye and evaporative dry eye. Sjögren’s syndrome dry eye (SSDE) is generally described as aqueous-deficient dry eye. However, as the leading pathophysiological mechanism of evaporative dry eye, meibomian gland dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Substantial evidence has confirmed the existence of the gut-eye axis. For instance, research has shown that CD-25 gene knockout mice exhibit symptoms resembling Sjögren’s dry eye, accompanied by alterations in microbiota composition, whereas these symptoms were mitigated after fecal transplantation ( 35 , 36 ). Peng et al demonstrated that the outer blood-retinal barrier and colonic epithelial barrier were impaired in murine with the Rd8 mutation of Crb1, facilitating the migration of GM from the lower gastrointestinal tract to the retina and secondary retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has confirmed the existence of the gut-eye axis. For instance, research has shown that CD-25 gene knockout mice exhibit symptoms resembling Sjögren’s dry eye, accompanied by alterations in microbiota composition, whereas these symptoms were mitigated after fecal transplantation ( 35 , 36 ). Peng et al demonstrated that the outer blood-retinal barrier and colonic epithelial barrier were impaired in murine with the Rd8 mutation of Crb1, facilitating the migration of GM from the lower gastrointestinal tract to the retina and secondary retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Standard treatment for EDE (i.e., MGD), also one of the prevalent conditions in SS patients, encompasses eyelid hygiene and warming. It is important to note that SS-related DED primarily involves tear deficiency, with secondary occurrences of MGD [ 19 , 35 ]. Even though artificial tears are extensively utilized globally and come in various formulations, there is a scarcity of studies that directly compare different types of artificial tears to determine their superiority [ 36 ].…”
Section: General Management Of Ded Associated With Ssmentioning
confidence: 99%
“…SS DED is commonly characterized by ADDE. Nonetheless, recent works of literature have reported that EDE also can occur in SS due to meibomian gland dysfunction (MGD) [ 18 , 19 ]. DED associated with SS presents a significant clinical challenge, impacting patient comfort and vision.…”
Section: Introductionmentioning
confidence: 99%
“…3) To manage a possible associated meibomian dysfunction. In this case, "eyelid care" is recommended to thin the meibum and restore secretion from the meibomian glands (23).…”
Section: Initial Managementmentioning
confidence: 99%